2005
DOI: 10.1002/ajh.20300
|View full text |Cite
|
Sign up to set email alerts
|

Severe pulmonary arterial hypertension as initial manifestation of intravascular lymphoma: Case report

Abstract: Intravascular lymphoma (IVL) is a rare and usually fatal disease that belongs to the class of high-grade malignant lymphomas and which is characterized by proliferation of neoplastic lymphoid cells exclusively within the lumina of small blood vessels. Its polymorphic and nonspecific clinical manifestations make antemortem diagnosis very difficult. We report herein a case of IVL revealed by fatal, precapillary, pulmonary arterial hypertension and associated with long-lasting fever. Extensive investigation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 17 publications
(28 reference statements)
0
27
0
2
Order By: Relevance
“…Proof of this supposition, however, can only come from extensive evaluation of integrin expression in IVL cases from disparate organs. Beyond these major presentations, there are single case reports of IVL presenting primarily in almost every organ system; as interstitial lung disease [18], adrenal failure [19], pulmonary hypertension [20], nephrotic syndrome [21], myocardial infarction [22], and symmetric polyarthritis [23].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Proof of this supposition, however, can only come from extensive evaluation of integrin expression in IVL cases from disparate organs. Beyond these major presentations, there are single case reports of IVL presenting primarily in almost every organ system; as interstitial lung disease [18], adrenal failure [19], pulmonary hypertension [20], nephrotic syndrome [21], myocardial infarction [22], and symmetric polyarthritis [23].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Although autopsy findings indicated that lung involvement in IVLBCL is relatively frequent (approximately 60%) (3,4), predominant or primary presentation in lung has been rare and only a few cases have been reported in the literature to date (4)(5)(6)(9)(10)(11)(12) (10,(14)(15)(16), three of the four cases with PAH lacked such lesions that could promote physicians to take account of lung biopsy. Thus, two cases could not be treated with chemotherapy due to lack of evidence of lymphoma, and they were diagnosed at autopsy (4,6). The present case is the only one that was successfully treated after a histological diagnosis of specimens taken from lung areas, despite the lack of findings of conventional radiographic measures.…”
Section: Discussionmentioning
confidence: 99%
“…PAH has been reported in patients with several hematological diseases including myeloproliferative [5] and lymphoproliferative disorders [6] as well as intravascular lymphoma (IVL) [7,8] . PAH is reportedly common among patients with myeloproliferative disorders or myelodysplastic syndromes, particularly among those with extremely elevated platelet counts.…”
Section: Discussionmentioning
confidence: 99%
“…As a mechanism for the development of PAH in such patients, the stimulation of vascular endothelial cells by platelet-associated factors, such as platelet-derived serotonin, platelet-derived growth factor, or transforming growth factor β, has been suggested. Furthermore, tumor emboli in the pulmonary arterial vasculature in cases with IVL remain an underlying cause of PAH [7,8] . In our case, no significant findings on imaging studies (CT and scintigraphy) were observed, excluding the presence of thromboemboli as a cause of the PAH.…”
Section: Discussionmentioning
confidence: 99%